THE EFFECTS OF INTEREST RATE ON REAL EFFECTIVE EXCHANGE RATE VOLATILITY SPILLOVER IN MALAYSIA AND THAILAND: EMPIRICAL EVIDENCE - Mohd Jaffri Abu Bakar; Nanthakumar Loganathan; Asan Ali Golam Hassan; Tirta Nugraha Mursitama (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2021)
The research examined this asymmetric effect between the interrelationship of the interbank rate on the external competitiveness purchasing power represented by the real effective exchange rate for Malaysia and Thailand using monthly data covering the period of 1994 until 2020. The empirical findings confirms an asymmetric effect between interbank rate and real effective exchange rate based on the nonlinear autoregressive distributed lag estimates. The research also finds a unidirectional asymmetric causal relationship running from real effective exchange rate on interbank rate Thailand, which indicate the monetary policy has a direct relationship on interbank rate volatility. While in Malaysia, there is no causality running between both variables since the country has proposed several soft monetary policies and more concentrating on the short-term borrowing by improving the tight money supply circulation based on the domestic inflation, global economic, and financial market volatility. Therefore, the research recommends a specific need of monetary stabilizer policy to stabilize both countries’ currencies and put more effort to liberalize the foreign exchange rate system in a globalized economy.